Liver Function Markers Response to Different Exercise Intensities in Athletes A Single Bout Perspective - Singh, Jagdeep; Chahar, Pradeep Singh; Singh, Samir Kumar; Mishra, Surendra Pratap; Meena, Anshul; Kumar, Ravi (Defence Life Science Journal, 2024)
Exercise provides considerable health advantages through promoting proper body system functioning, healthy growth and development, and quality of life. The present study investigated the effect of single bout High- Intensity Exercise (HIE) compared to Low-Intensity Exercise (LIE) on liver function markers in athletes. This cross-sectional study was carried out in the Department of Physical Education, Banaras Hindu University, Varanasi (UP). A total of 20 healthy male athletes with age range from 22 to 26 years were randomly selected and underwent 5 minutes of HIE and LIE separated by one week. Blood samples for selected liver function markers were taken pre-exercise, immediately, 10 and 20 minutes post-HIE and LIE, respectively. A repeated measures ANOVA with greenhouse-geisser correction found a significant difference between high and low intensity exercises for SGOT (F=5.881; p<0.05) and SBT (F=7.154; p<0.05) values, while statistically insignificant in the case of SGPT (F=1.572; p>0.05). In high intensity exercise there was statistically significant difference for SGOT (F=7.564; p<0.05) value between different time points. Post hoc analysis with a bonferroni correction showed that SGOT value was significantly increased immediately after the HIE, reducing 10 minutes after the exercise and closely returned to baseline level after 20 minutes of exercise, whereas LIE showed no significant changes. Exercise intensity is important as it triggers liver pathology by asymptomatic modifying liver function markers. These findings can be used to develop and administer exercise training plans for athletes.